Unlocking insights: exploring mammography beliefs among Teshie community mothers – a qualitative exploratory descriptive study - Priscilla Yeye Adumoah Attafuah; Evans Appiah Osei; Lauraine Watson-Quartey; Jamilatu B Kappiah; Ronald Odonkor; Hawah Amadu Toure; Nana Semuah Bressey; Collins Sarpong (BMJ Open)
Background Breast cancer is a global concern, especially for women of African descent, with rising cases in Ghana. While awareness and diagnostic screening have improved, studies in Ghana and many African countries have prioritised breast self-examinations, with limited focus on mammography.Objective Our study explores beliefs and attitudes towards mammography screening among mothers at Teshie Community in Ghana.Methods The study methodology was qualitative and an exploratory design was used. Convenience sampling was used to select 30 participants until saturation was reached. Indepth, one-on-one interviews were conducted with a semistructured interview guide with probes until saturation was reached. Then data were audiotaped audiotaped, transcribed and coded. Content analysis was done to generate themes and subthemes.Findings Most participants, 93%, had not undergone mammography screening. Only two individuals (7%) had experienced mammography screening. The study identified two major themes: beliefs and perceptions regarding mammography, and attitudes towards mammography screening. Participants generally displayed limited knowledge of mammography screening, along with mixed attitudes and varying degrees of motivation. Notably, many participants enjoyed strong spousal support for mammography screening.Conclusion It was recommended that nurses should create awareness of mammography to increase the knowledge of women and the general population about mammography, as this is believed to increase the uptake of mammography screening.